Knowledge about non-adherence to contraceptive methods Could it decrease mortality? Conocimiento sobre la no adherencia de métodos anticonceptivos ¿Podría disminuir la mortalidad? - Gramajo Cortez, Luis Facundo (2023)
Introduction: In Peru, 78.1% of women between the ages of 15 and 49 use a contraceptive method, which is diminished by various factors associated with non-adherence to the contraceptive method, thus producing unwanted pregnancies and the spread of sexually transmitted diseases. Objective: To determine the factors associated with non-adherence to contraceptive methods in women of childbearing age in Peru according to ENDES 2021. Methods: Observational, analytical and cross-sectional study. The information used is found in the ENDES 2021 public database. The population of this research is made up of Peruvian women between the ages of 15 and 49. Statistical analysis was performed with the statistical program SPSS version 26.0. The qualitative variables were represented in a univariate table with frequencies and coefficients of variation. The approved statistical significance value was p <0.05 with 95% confidence intervals. Results: 43.7% of women did not adhere to the contraceptive method. There was a significant association for the variables: area of rural residence (Rpa 1.05 IC 1 – 1.1), separated marital status (Rpa 1.1, IC 1 – 1.1), widow marital status (Rpa 1.3, IC 1.1 – 1.5), cohabiting marital status ( Rpa 1.1, IC 1.1 – 1.2) , poor wealth index (Rpa 1.03, IC 0.9 – 1.0) Conclusions: The factors associated with non-adherence to contraceptive methods in women of childbearing age in Peru, which are significantly associated are: Rural area of residence, separate marital status, widow and cohabitant and have a poor wealth index.